Enhancing Public Confidence in Financial Reporting: The Role of Corporate Governance - Ebele, Anyadiegwu Peace; Sunday, Anichebe Alphonsus (European Journal of Business and Strategic Management, 2016)
Purpose: This study is set out to investigate the "Role of Corporate Governance in Enhancing Public Confidence in Financial Reporting". Methodology: Relevant data were collected from the Central Bank of Nigeria, using a well-structured questionnaire. The statistical technique for data analysis and test of hypothetical proposition was Pearson product coefficient of correlation(r.) Results: The result of the findings revealed that there is significant relationship between the board structure, role /responsibilities and credibility of financial reports. Audit committee plays a significant role in monitoring and promoting the credibility of financial reports. Also, ownership structure of the firm has significant impact on the credibility of financial reports. Study conclusion and policy recommendations: The study concluded that Corporate Governance is necessary to the proper functioning of banks and that Corporate Governance can only prevent bank distress only if it is well implemented. Finally the study recommends: that corporate governance should be used as a tool to help stem the tide of distress, as it entails conformity with prudential guidelines of the government; the Central Bank and NDIC should enforce the need for all banks to have approved policies in all their operation areas and strong inspection division to enforce these policies; that government owes the country a patriotic duty to establish and sustain macroeconomic stability in order for the banking system to perform at its optimum capacity , economic and political stability can help prevent bank distress and more importantly, is the need for qualified staff in the banking system as this will enable the utilization of expertise, skill and care in the performance of duties by staff, this will lead to better performance.